PARAMETERS OF THE SEPARATOR-CLEANING DEVICE (Scientific journal of the Fergana State University, 2024)
Optimization of the structure of the separator device, as well as improvement of the separator-cleaner drums installed in the air transport system. In addition, the analysis of the equipment for cleaning cotton from small impurities used in cotton ginning enterprises, the principle of operation of this new unit, the rotation speeds of the transmissions that move it and their changes in cotton quality. 'secret has been analyzed.